Landrive / Rasyiqatul Athirah Azmizan … [et al.] - Azmizan, Rasyiqatul Athirah; Zolkepli, Nurul Syaeerah Ayuni; Tamirin, Nurul Batrisyia; Daud, Nurul Aliah Syafiqah; Wei Loon, Koe (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
In this advanced technology era, the innovation of everyday things is highly participated in. Although the existing On-The-Go (OTG) pen drives out there are able to connect with other devices such as tablets and smartphones, they only offer one type of universal serial bus (USB). Landrive, our product’s brand name is being introduced by our company, Gadgetegy. Landrive is an On-The-Go (OTG) pen drive made with features that have four types of universal serial bus (USB); USB Type A, Micro USB, USB Type C and Lightning USB which are compatible with various gadgets such as laptop/computer, MacBook and smartphone. It is designated to be a convenient tool specifically for students and corporate workers who use lanyards in their daily lives. The lanyard can be customized with different designs and colors based on customers' requests. In addition, polyester, which is a high quality of material is being used to produce the lanyard which the user will feel comfortable wearing it around their neck. Furthermore, it can prevent misplacing and make it easy to bring it everywhere. Thus, Landrive is able to help users save time, space, and also the environment. Therefore, it could be marketable as it is able to solve customer problems especially for busy people like students and corporate workers.